2021
DOI: 10.1039/d1cc01273h
|View full text |Cite
|
Sign up to set email alerts
|

Lewis base-free thiophosphonium ion: a cationic sulfur atom transfer reagent

Abstract: Phosphorus(V) sulfide and Lawesson’s reagent are commonly used thionating reagents which are considered to operate after dissociation into highly reactive dithiophosphorane fragments. We report the synthesis and properties of a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The synthesis of the terminal diprotic methylene phosphonium ions [4a] + and [4b] + was realized by oxidation of the methylsubstituted phosphines to phosphonium salts and subsequent deprotonation, analogous to the original synthesis by Grützmacher (Scheme 2). 37 Sterically demanding N-heterocyclic imines (NHIs) have been shown to be effective for the kinetic stabilization of low-coordinate phosphorus(V), 25,[38][39][40][41][42] and other main group cations. 43 Moreover, Schoeller predicted that nitrogen-based p-donor substituents at phosphorus effectively increase the singlet-triplet gap of phosphinocarbenes.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the terminal diprotic methylene phosphonium ions [4a] + and [4b] + was realized by oxidation of the methylsubstituted phosphines to phosphonium salts and subsequent deprotonation, analogous to the original synthesis by Grützmacher (Scheme 2). 37 Sterically demanding N-heterocyclic imines (NHIs) have been shown to be effective for the kinetic stabilization of low-coordinate phosphorus(V), 25,[38][39][40][41][42] and other main group cations. 43 Moreover, Schoeller predicted that nitrogen-based p-donor substituents at phosphorus effectively increase the singlet-triplet gap of phosphinocarbenes.…”
Section: Resultsmentioning
confidence: 99%
“…Cationic LA based on free oxophosphonium cation (Scheme 52) featuring trigonal planar arrangement of P‐atom and FIA of 634 kJ mol −1 was reported by Dielmann in 2018 [187] . Analogous thiophosphonium LA (FIA 616 kJ mol −1 ) was reported in 2021 [188] …”
Section: Novel Lewis Acids and Lewis Superacidsmentioning
confidence: 94%
“…[187] Analogous thiophosphonium LA (FIA 616 kJ mol À 1 ) was reported in 2021. [188] Reactivity of these oxophosphonium I + and thiophosphonium II + cationic Lewis acids towards MeCN and Py was studied by tensimetry method and computationally. [82] It was demonstrated that I[BArF 24 ] forms a thermally stable 1 : 1 complex with pyridine, while II[BArF 24 ] forms a labile complex with pyridine.…”
Section: Silicon Lewis Superacidsmentioning
confidence: 99%
“…38,39 Recently, we explored the cycloaddition reaction between oxophosphonium cations and alkynes and showed that by using strong π-donor substituents instead of alkyl groups at the phosphorus atom, the "closed" oxaphosphete and the "open" 1-phospha-4-oxa-butadiene get closer in energy. 40 Enabled by our recent success in isolating the first Lewis-base-free thiophosphonium ion [R 2 P=S] + , 41 we herein report on [2 + 2]-cycloaddition reactions of thiophosphonium salts with alkynes, yielding 1,2-thiaphosphete cations (Scheme 1b). The first neutral P V 1,2thiaphosphete was synthesized by Kawashima and co-workers containing a P-center stabilized by the Martin ligand (Scheme 1, I).…”
Section: ■ Introductionmentioning
confidence: 99%